A novel device for greater precision and safety in open-wedge high tibial osteotomy: cadaveric study - Ribeiro, Cristiano Hossri; Mod, Mauricio Sante Bettio; Isch, Daniel; Baier, Clemens; Maderbacher, Guenther; Severino, Nilson Roberto; Cataneo, Daniele Cristina [UNESP] (Springer Nature, 2020)
Introduction: The complications of the open-wedge osteotomy technique (slope, hypo- and hypercorrection and fractures) are related to difficulties in the control of the open-wedge angle during surgery. Materials and methods: In this cadaveric study, we evaluated the safety and precision of a novel system, the Realignment High Control System (RHC), in the correction of knee mechanical axis and slope. The RHC has a fixation plate coupled to a dynamic device that opens the osteotomy continuously, allowing plate fixation before osteotomy wedge opening. Results: All procedures were easily performed, with no fractures. The openings equaled the indicated by the navigation system for 7.5° and 10°, and for 5°, there was a statistically, although not clinically significant, difference of 0.6°. The slope shown by the RHC setting and in the navigation system was significantly different for the 10° setting only, with a mean difference of 0.563°. Conclusions: RHC facilitates the surgical technique of high tibial osteotomy, with gradual wedge opening, precise correction of the mechanical axis, and appropriate control of the tibial slope, even with larger openings.
Keywords: Computer-assisted surgery; Genu varum; High-tibial-osteotomy; Knee osteoarthritis; Surgical technique